How a Good Sleep Predicts Life Satisfaction: The Role of Zero-Sum Beliefs About Happiness - Shin, Ji-eun; Kim, Jung Ki (Frontiers in Psychology, 2018)
Sleep, although a vital aspect of human functioning, has received scant attention in happiness research. This research examines the effect of sleep quality on life satisfaction, and one possible mechanism that bridges the two. One cognitive factor that might tie the relationship between sleep and life satisfaction is a belief about the (in) finite nature of happiness (zero-sum belief about happiness; ZBH), a mindset that occurs more under conditions of scarcity. Given the interconnections among experiences prompted by various types of scarcity (e.g., financial, calorie), we predicted that deprived cognitive resource caused by poor sleep may activate the ZBH, thereby hurting one’s life satisfaction. As expected, we found that sleep quality promoted the participants’ life satisfaction, even controlling for baseline variables. More importantly, this relationship was partially mediated by ZBH. This study opens interesting questions on a relatively unexamined role of non-social predictors, such as sleep, in well-being.